2013
DOI: 10.4172/2157-7412.1000205
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Regulation of Interferon Regulatory Factor Expression: Implications in Human Malignancies

Abstract: Originally identified as regulators of the type I Interferon system, the nine mammalian members of the Interferon Regulatory Factor (IRF) family are transcriptional regulators with multiple biologic functions, among which the best known are those involved in initiating and regulating many aspect of host immunity, downstream pattern recognition receptors in response to cell injuries. In addition, these versatile proteins also regulate cell differentiation, cell growth and apoptosis in several cell types, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 172 publications
0
1
0
Order By: Relevance
“…Interferon-inducible protein p78 5-Aza-dC Kulaeva et al, 2003 suppressor genes. No wonder that IRFs can carry both genetic and epigenetic modifications, and their interrelations with the IFN unresponsiveness and association with tumour progression have been described in a number of studies (Fragale et al, 2013). Analysis of a number of tumour cell lines revealed that particular IRFs were differentially expressed in various gastric cancer cells, and frequent suppression of IRF4, IRF5 and IRF8 was documented (Yamashita et al, 2010).…”
Section: Mx1mentioning
confidence: 99%
“…Interferon-inducible protein p78 5-Aza-dC Kulaeva et al, 2003 suppressor genes. No wonder that IRFs can carry both genetic and epigenetic modifications, and their interrelations with the IFN unresponsiveness and association with tumour progression have been described in a number of studies (Fragale et al, 2013). Analysis of a number of tumour cell lines revealed that particular IRFs were differentially expressed in various gastric cancer cells, and frequent suppression of IRF4, IRF5 and IRF8 was documented (Yamashita et al, 2010).…”
Section: Mx1mentioning
confidence: 99%